2020
DOI: 10.3390/w12030888
|View full text |Cite
|
Sign up to set email alerts
|

Springing for Safe Water: Drinking Water Quality and Source Selection in Central Appalachian Communities

Abstract: Issues surrounding water infrastructure, access, and quality are well documented in the Central Appalachian region of the United States. Even in cases where residents have in-home piped point-of-use (POU) water, some rely on alternative drinking water sources for daily needs—including water collection from roadside springs. This effort aims to better understand and document spring usage in this region by identifying the factors that influence drinking water source selection and comparing household and spring w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 32 publications
(48 reference statements)
0
21
0
Order By: Relevance
“…Such observations extend not only to rural regions outside of Alaska but also to the urban fringe globally . Across the US, clusters of communities lack sustainable access to in-home water services, including those at the Texas–Mexico border (the Colonias), the Navajo Nation, and the Appalachian region. , And beyond the US, there are several remote Arctic communities in Canada, , Greenland, and Russia that also face similar water access and water security challenges. Overall, this work presents a framework that can be used in other water-insecure regions in the U.S. and beyond to assess drivers of residential water costs to provide a comparative benchmark and to help identify factors that can drive policy.…”
Section: Resultsmentioning
confidence: 92%
“…Such observations extend not only to rural regions outside of Alaska but also to the urban fringe globally . Across the US, clusters of communities lack sustainable access to in-home water services, including those at the Texas–Mexico border (the Colonias), the Navajo Nation, and the Appalachian region. , And beyond the US, there are several remote Arctic communities in Canada, , Greenland, and Russia that also face similar water access and water security challenges. Overall, this work presents a framework that can be used in other water-insecure regions in the U.S. and beyond to assess drivers of residential water costs to provide a comparative benchmark and to help identify factors that can drive policy.…”
Section: Resultsmentioning
confidence: 92%
“…Some of the comments from our survey indicate that those on well water have problems with organoleptic and aesthetic properties, such as hydrogen sulfide (rotten egg) odors or staining from iron. Patton et al (2020) surveyed homeowners near roadside springs in three Appalachian states (Kentucky, Virginia, and West Virginia) with in‐home well water, and reported that over 80% of those surveyed did not trust their tap water for aesthetic reasons. The aesthetic properties of the water from the springs in our study are excellent: the water is clear, cold, and has no undesirable taste or odor.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, water from the springs has the potential to contain dissolved constituents or host micro‐organisms that can pose threats to human health. Our understanding of roadside spring use and water quality is not well documented and only recently have there been any published studies (Swistock et al 2015; Westhues 2017; Krometis et al 2019; Patton et al 2020). There has been at least one parasitic outbreak linked to a spring in upstate New York (Bedard et al 2016).…”
mentioning
confidence: 99%
“…In these communities, funding an in-home reuse system could be more affordable than traditional systems. In the contiguous United States, high capital costs also hinder access to in-home water services in the Navajo Nation, Appalachia region, , and the Colonias in Texas . The COVID-19 pandemic has highlighted the disproportionate health impacts in Tribal communities throughout the United States owing to lack of access to in-home water services .…”
Section: Discussionmentioning
confidence: 99%